THE ROLE OF THE ASSOCIATIVE METHOD IN THE ASSESSMENT OF NEW KNOWLEDGE FOR STUDENTS (Academia Science Repository, 2023)
Pedagogical practice shows that it is difficult for a student who has decided what profession he will become, to master the subjects of another subject [1,3,5]. First of all, there is a lack of desire and motivation, which extinguishes interest in science from the very first days. This small study investigated the effectiveness of non-traditional teaching methods [2,4].